Study on Creep Property of Vortex Spun Yarn (Journal of Fiber Bioengineering and Informatics, 2009)
Based on the Hook's law for infinitesimal strains and Newton's law for infinitesimal rates of strain, the creep property of vortex spun yarn is studied by generalized Maxwell model connected in a row to a Hook's spring. The results show that this model can effectively explain the creep property of vortex spun yarn. For different creep test conditions, firstly, the creep elongation increases sharply with the prolongation of creep time, and then slows down after a constant elongation period. The maximal creep elongation after being stressed by a constant force value increases with the increase of the elongation rate. When the tensile level is higher, the maximal elongation is larger under a constant elongation rate. Moreover, the maximal creep elongation is larger for a finer vortex spun yarn.
Keywords: Murata Vortex spinning (MVS); vortex spun yarn; viscoelastic model; creep properties